2021
DOI: 10.31557/apjcp.2021.22.1.241
|View full text |Cite
|
Sign up to set email alerts
|

Doctor-Patient Cancer Screening Communications among Church-based Chinese Adults – The Role of Caregiver Experience and Family History

Abstract: Rationales for conducting cancer communication study in Chinese ImmigrantsChinese-American is the largest Asian subpopulation (23.0%), with over two-thirds as first-generation immigrants born overseas (ACS, 2016). However, current research show Chinese-American is under-represented in cancer studies and reported low screening adherence. With complex barriers towards cultural, language, and healthcare access, Chinese immigrants face deepened disparities in cancer screening participations (Sentell et al., 2015;H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Designing culturally-sensitive interventions that target these barriers may improve cervical test rates among Asians. Potential strategies to enhance screening rates in non-Hispanic Asians could include community-based or workplace-based group educational programs, enhancing cultural awareness among healthcare professionals, and partnering with outreach workers to overcome language and cultural barriers [ 114 , 115 ]. One cluster-randomized controlled trial demonstrated that community health worker-led health-literacy intervention, involving personalized health-literacy training, cancer-screening brochures, and monthly telephone counseling, significantly increased cervical (OR: 13.3, 95% CI: 7.5–22.3) screening uptake and positive perceptions about cancer screening among Korean-American women [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…Designing culturally-sensitive interventions that target these barriers may improve cervical test rates among Asians. Potential strategies to enhance screening rates in non-Hispanic Asians could include community-based or workplace-based group educational programs, enhancing cultural awareness among healthcare professionals, and partnering with outreach workers to overcome language and cultural barriers [ 114 , 115 ]. One cluster-randomized controlled trial demonstrated that community health worker-led health-literacy intervention, involving personalized health-literacy training, cancer-screening brochures, and monthly telephone counseling, significantly increased cervical (OR: 13.3, 95% CI: 7.5–22.3) screening uptake and positive perceptions about cancer screening among Korean-American women [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 LHWs have been defined as members of the community who have received some training to promote health or to perform some health care services but who are not health care professionals. 16,36,[41][42][43] LHWs potentially could assist in symptom screening, transportation coordination, distress screening, and leading health discussions. 16,41,42 Lay Health Educators are members of the community and are qualified as community connectors because they live in the communities in which they work, understand what is meaningful to those communities, communicate in the language of the people in their community, and recognize and incorporate social buffers.…”
Section: Existing Occupational Identitiesmentioning
confidence: 99%
“…They are described as CHWs who are well versed in cultural norms or who recognize and address community‐specific barriers 14,15,39 and are selected based on their involvement in their community as well as their existing knowledge of certain cancers and diseases 40 . LHWs have been defined as members of the community who have received some training to promote health or to perform some health care services but who are not health care professionals 16,36,41‐43 . LHWs potentially could assist in symptom screening, transportation coordination, distress screening, and leading health discussions 16,41,42 .…”
Section: Existing Occupational Identitiesmentioning
confidence: 99%
“…Consequently, implications of low-quality patient-provider communication potentially may lead to decreased use of preventive services, lack of medical follow-up, higher rates of hospitalization, and drug complications 13. In the cancer screening literature, there has been substantial evidence showing that provider recommendation significantly improves cancer screening rates14; however, some studies have found alarmingly low provider-patient cancer screening communication 15. For Asians, a provider recommendation is the leading predictor of adherence to cancer screening 16,17.…”
Section: Why Do Asian Patients Continuously Have the Lowest Quality O...mentioning
confidence: 99%
“…13 In the cancer screening literature, there has been substantial evidence showing that provider recommendation significantly improves cancer screening rates 14 ; however, some studies have found alarmingly low provider-patient cancer screening communication. 15 For Asians, a provider recommendation is the leading predictor of adherence to cancer screening. 16,17 Therefore, culturally and linguistically appropriate, patientcentered strategies must be implemented to optimize highquality patient-provider communication 16 that will result in eliminating health disparities and improving health outcomes.…”
mentioning
confidence: 99%